Capacity analysis of high-throughput satellite links for Earth observation missions - Katona, Zoltán; Kourogiorgas, Charilaos; Panagopoulos, Athanasios D.; Jeannin, Nicolas (International journal of satellite communications and networking, 2015)
Summary Earth observation missions are important for economy and science. The data collected by such satellites are used in agriculture, maritime services, disaster and environmental monitoring, and so on. Earth observation satellites are low Earth orbit (LEO) satellites typically with a sun‐synchronous, polar orbit. The amount of collected data has significantly increased over the years. This calls for finding new ways to increase the transfer rate on the satellite link. As a consequence, the present paper analyzes the possibility of moving from low to high radio frequencies. In addition, different topologies are analyzed, such as the conventional direct LEO satellite to ground station link, and the data relay link from the LEO satellite to the ground station through a geostationary Earth orbit (GEO) satellite. The present paper thus analyzes the foreseeable performance of Ka‐band and Q‐band direct links, and Ka‐band, Q‐band, and W‐band data relay links. The following channel adaptation techniques were assumed during the analysis: adaptive coding and modulation and variable coding and modulation. According to the results, the link margin is significantly high in clear sky, reaching at least 7dB, even using the least robust modulation and coding (ModCod) scheme, which applies 1024‐amplitude and phase‐shift keying (1024‐APSK) modulation scheme. As a consequence, it shall be important in the future to further increase the spectral efficiency of the link, by, for example, reducing phase noise in order to enable even higher‐order modulation schemes. Copyright © 2015 John Wiley & Sons, Ltd. Earth observation satellite missions are important for economy and science. The data collected by such satellites are used in agriculture, maritime services, disaster and environmental monitoring, and so on. The present paper analyzes the foreseeable performance of Ka‐band and Q‐band direct links, and Ka‐band, Q‐band, and W‐band data relay links. The following channel adaptation techniques were assumed during the analysis: adaptive coding and modulation and variable coding and modulation. Even using the least robust ModCod, significant link margin remains.